Capabilities of cermets tools for high speed machining of austenitic stainless steel - Khan, Ahsan Ali; Salama Hajjaj, Sami (Asian Network for Scientific Information, 2006)
Cermets tools have very high hot hardness together with a low coefficient of friction, which facilitates machining at high speeds. In the present work cermet tools coated with titanium nitride were used to turn austenitic stainless steel at speeds between 300 and 700 m min-1. Feed rates were varied between 0.05 to 0.4 mm rev-1. Depth of cuts were between 0.1 and 0.5 mm. After machining, tool flank wear and the cutting edges were observed using Scanning Electron Microscope (SEM). The experimental results showed that when cermet inserts were used for finishing cuts, very fine surfaces were produced. However, when used for roughing cuts, they tended to fracture unpredictably rather than having gradual flank wear. Thus, the cermet tools were found to perform satisfactorily only for finishing operations with feed rates ranging between 0.1 and 0.2 mm rev-1 and at the maximum depth of cut of 0.3 mm. For stable operations, the maximum cutting speed should be below 600 m min-1; exceeding this limit resulted catastrophic failure of the cutting edge.